The response of Eucalyptus grandis to drought stress, rewatering and combined stress involving Chrysoporthe austroafricana infection - Naidoo, Sanushka (University of Pretoria, 2024)
Thesis (PhD (Biotechnology))--University of Pretoria, 2024.